Economic development of ultra small peripheral regions of West Europe (Case of Aland and Faroe islands) - Elena Efimova; Natalia Kuznetsova (European Regional Science Association (ERSA), 2014)
The article deals with the problem of West European and Nordic countries small economies as well as ultra-small autonomous territories of Alands and Faeroes island's development. The latter are considered as the «competitive sub-peripheries» areas due to the special industrial organization development, stimulated by the national and the EU economic policy. A special status of these territories causes their conversion into the transport-logistics, informational, financial bridges between different European regions and countries. The primary goal of the article is the identification of ultra-small territories, revealing features of economic development and the modern business status in economic history context of small economies classification. The object of investigation is focused on West European and Nordic countries small economies as well as ultra-small autonomous territories of Aland and Faeroe islands affiliated to Finland and Denmark respectively. The hypothesis of the article is that ultra-small autonomous territories under consideration are developing as the «competitive sub-peripheries» areas due to the special industrial organization development, stimulated by the national and, partially, the EU economic policy supporting economic growth of both autonomous. Ultra-small territories of small states under consideration are developing as the «competitive peripheries» areas due to the special Scandinavian capitalist model development characterized by high level of social capital. The methods of the article deal with analysis-synthesis, historical and logical methods of investigation, and methods of international comparisons. The main summing up conclusion is that Aland and Faeroe islands are converting nowadays into the transport-logistics, informational, financial bridges between different European regions and countries. The autonomous territories are the experimental laboratory of the European and world economy due to the specific model of their social-oriented economic growth.
Keywords: F23; F43; R11; R58; 330; ultra-small regions; spatial development; competitive (sub)periphery; industrial organization; economic policy